2022
DOI: 10.3390/ani12111383
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Nicotinic Acid Elevates NAD+ Precursors in the Follicular Fluid of Mares

Abstract: A deficiency in NAD+ has previously been linked with increased occurrences of congenital abnormalities and embryonic death in humans and mice. Early embryonic death is a major factor involved in pregnancy loss in mares, and very little is known regarding the NAD+ requirements for optimum reproductive function in horses. The aim of this study was to determine the effect of supplementing the diet of mares with nicotinic acid (NA) on the composition of NAD+ metabolites in the blood and follicular fluid. Vehicle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Bertolo et al found a decrease in NAD(P)H levels in 12-month-old aged mice, but this decrease occurred only in oocytes and not in the entire ovary [ 32 ]. Studies conducted on other species such as porcine follicles [ 33 ], equine follicles [ 34 ], and humans [ 35 ] have shown similar results with age-related decreases in NAD + . All these results indicate that NAD + is closely related to ovarian aging and that the maintenance of NAD + levels in the follicles are necessary to ensure normal ovarian development.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 77%
“…Bertolo et al found a decrease in NAD(P)H levels in 12-month-old aged mice, but this decrease occurred only in oocytes and not in the entire ovary [ 32 ]. Studies conducted on other species such as porcine follicles [ 33 ], equine follicles [ 34 ], and humans [ 35 ] have shown similar results with age-related decreases in NAD + . All these results indicate that NAD + is closely related to ovarian aging and that the maintenance of NAD + levels in the follicles are necessary to ensure normal ovarian development.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 77%
“…Secondly, nicotinate and nicotinamide are two forms of vitamin B3, important precursors for the synthesis of NAD+ and NADP+, which play key roles in many biological processes, including energy metabolism and DNA repair [99]. In the ovaries, NAD+ and NADP+ may influence follicle maturation and ovulation [100]. Therefore, HCG may influence ovarian development by altering the nicotinate and nicotinamide metabolism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Collins et al reported that NA is a more favorable precursor than nicotinamide (NAM) in the liver, intestine, and kidneys [52]. NA supplementation increases the bioavailability of NAD + precursors in the follicular uid of the dominant follicle, which contributes to improved oocyte quality, especially in older oocytes [53]. In addition, NA treatment had a more favorable action in correcting meiosis in high-fat diet (HFD) mouse oocytes compared to nicotinamide mononucleotide (NMN) [54].…”
Section: Discussionmentioning
confidence: 99%